The Effects of N-terminal Mutations on β-amyloid Peptide Aggregation and Toxicity. (21st May 2018) - Foroutanpay, B.V.; Kumar, J.; Kang, S.G.; Danaei, N.; Westaway, D.; Sim, V.L.; Kar, S.
Highlights: Rodents may not develop Alzheimer disease due to sequence differences in β-amyloid. Humanizing rat β-amyloid reduced fibril but preserved oligomer formation. Oligomers had toxicities in rank order: human > rat ≫ mutant β-amyloid. Cell toxicity was influenced by N-terminal mutations of β-amyloid. Abstract: Human amyloid β1–42 (hAβ1–42) peptides are known to self-aggregate into oligomers that contribute to the degeneration of neurons and development of Alzheimer's disease (AD) pathology. Unlike humans, rodents do not develop AD, possibly due to differences in three amino acids (R5G, Y10F and H13R) within the hydrophilic N-terminal domain of Aβ1–42. This is partly supported by evidence that hAβ1–42 is more prone to fibrillization and has a higher cellular toxicity than rodent Aβ1–42 (rAβ1–42). Mutagenesis studies, however, have shown that correlation between fibrillization potential and toxicity is not always direct. Thus, to understand better how N-terminal mutations can affect hAβ1–42 toxicity through oligomerization, we evaluated fibrillization kinetics, oligomer sizes and toxicity profiles of double mutant (human toward rodent) Aβ1–42. Additionally, we tested the mutant peptides in combination with hAβ1–42, to assess effects on hAβ1–42 aggregation/toxicity. Our results clearly show that double mutations to humanize rAβ1–42 result in a significantly reduced efficiency of fibril formation, as determined by Thioflavin-T aggregation assays and confirmed with electron micrographic studies. Interestingly, the mutants are still able to aggregate into oligomers, which are predominantly larger than those comprised of hAβ1–42. Our cell viability experiments further showed a rank order of oligomer toxicity of hAβ1–42 > rAβ1–42 ≫ mutant Aβ1–42, suggesting that toxicity can be influenced by N-terminal Aβ1–42 mutations via reduction of fibril formation and/or alteration of oligomer size. These results, taken together, confirm that N-terminal mutations can affect Aβ fibril and oligomer formation with reduced toxicity despite lying outside the core amyloid region of Aβ peptide.